Qualitative research design - Tajuddin, Nor Azlin (2013)
This is a half-day qualitative workshop designed for medical practitioners of Paediatrics Palliative Care Unit of USM Kubang Krian. Topics covered in the workshop include stages of qualitative research, data collection techniques, data analysis and report writing.